Keterlibatan Kaum Bangsawan dalam Pemilihan Kepala Daerah (Pilkada) di Kabupaten Pinrang Provinsi Sulawesi Selatan - Muchlas M. Tahir; FitrianiSari Handayani Razak; Zulfan Nahruddin. (Universitas Muhammadiyah Ponorogo, 2017)
Pilkada became a space that presents the elite of the community, but behind the contestation of the phenomenon is quite interesting when people are faced with a dilemma where the elite who compete are the descendants of nobility.This study used a qualitative approach to explainingd main problems discussed by descriptive method. The fact is Strang Bugis society community, always have a desire to domination power and not hesitate to mutually contest between the group. The fact that Andi's group who contested in the arena of elections is inseparable from these three things: First, the building construction of the Andi's behavior in the society structure becomes the determinant to get the voters sympathy. Second, look at the capital in the Andis as a means to contest the winner, the capital's most powerful capital and also in the sense of being. Third, the habitus and capital will affect Andi's victory in which the arena of Pilkada as a container or to play the habitus and capital. These three things became the determinant of the winning process of the actor who was contesting in the arena of elections.